1995
DOI: 10.1136/bjo.79.4.306
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of non-resectable malignant iris tumours with custom designed plaque radiotherapy.

Abstract: Background-Plaque radiotherapy is the most common method of managing posterior uveal melanoma but its use for iris melanoma and iris metastases has not yet been evaluated. Methods-Fourteen patients with nonresectable iris melanoma and four with iris metastasis were treated with plaque radiotherapy. The tumour response to treatment and the local side effects of the radioactive plaque were evaluated. Results-In the iris melanoma group over a mean follow up of 26 (range 6-75) months, the tumour regressed in 13 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 29 publications
0
42
1
1
Order By: Relevance
“…The first group of iris melanoma patients treated with plaque radiation therapy with iodide (I-125) was reported in 1995 (Shields et al 1995). These patients showed a good tumour control and few side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first group of iris melanoma patients treated with plaque radiation therapy with iodide (I-125) was reported in 1995 (Shields et al 1995). These patients showed a good tumour control and few side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Keunen, 2 initially introduced for posterior uveal melanoma in 1960s, had until recently not been used for anterior uveal melanoma in view of potential risks of radiation on the cornea and lens. In 1995, Shields et al were the first to report about the treatment of iris melanomas with plaque radiation therapy using iodide-125 with a good tumour control (Shields et al 1995), followed by reports on the effectiveness of palladium-103 and other plaques (Finger 2001;Shields et al 2003). The first abstract of ruthenium-106 (Ru-106) plaque brachytherapy for iris melanomas in a cohort of 24 consecutive patients with a short follow-up was presented by our group (Kuipers et al 2002;Keizer et al 2004).…”
Section: Ruthenium Plaque Radiation Therapy For Iris and Iridociliarymentioning
confidence: 99%
See 1 more Smart Citation
“…Shields et al 6,7 reported on the outcome of using iodine-125 plaque radiotherapy for iris melanoma in 1995 and 2003. The incidence of cataract formation was found to be 70%.…”
Section: Discussionmentioning
confidence: 99%
“…2 In cases of unresectable iris melanoma or in tumours with extensive seeding, plaque radiotherapy, proton beam irradiation, or enucleation can be used. [6][7][8] Enucleation is the treatment of choice in cases of diffuse melanoma where more than half of the iris and trabecular meshwork are invaded by tumour or when there is uncontrollable glaucoma.…”
Section: Introductionmentioning
confidence: 99%